Analisis Kebutuhan Media Pembelajaran Berbasis Gamifikasi pada Mahasiswa Calon Guru (Jurnal PGSD Universitas Lamappapoleonro, 2025)
This type of research is quantitative descriptive. This research aims to obtain an analysis of the needs of gamification-based learning media in prospective teacher students. The subjects of this study consisted of 52 students in the elementary school teacher education study program of Lamappapoleonro University. The method used in this study is a survey method using a questionnaire instrument. The data obtained was then analyzed using quantitative descriptive analysis techniques. The results of this study show that the analysis of gamification-based learning needs in prospective teacher students is 53.75%. These findings indicate that students have a positive interest and readiness for the use of gamification-based learning media in the lecture process. Gamification media is seen as able to increase learning motivation, active involvement, and a more interesting learning atmosphere. Therefore, the results of this research can be used as a basis for the development of gamification-based learning media that is in accordance with the needs and characteristics of prospective teacher students